Impact of ICTs on Innovation Activities: Indication for selected European countries - Zoroja, Jovana (Naše gospodarstvo/Our economy, 2016)
The development and usage of information and communication technologies (ICTs) has particularly increased in the last two decades, while at the same time showing great potential to improve the efficacy of business processes, facilitate and drive innovations, and therefore increase competitiveness. Innovation activities represent an important factor for social and economic change as well as for increasing competitive advantages at both the national and firm levels. This paper focuses on the role that ICTs play in the innovation performance of selected European countries. Using data drawn from the Eurostat and Global Competitiveness Index (2007–2011) and panel regression analysis, research results indicate that ICTs have a significant impact on business innovation activities.